“You get the money after waiting for long and you get less than you anticipated”: Experiences of persons with disabilities in accessing the district special grant in Uganda - Ojok, Patrick; Mukasa, Joseph (Indonesian Journal of Disability Studies, 2024)
In 2010, Uganda scrapped an ambitious tax incentive provision in the Persons with Disabilities Act, 2006 that had allowed employers to claim up to 15% tax reduction in annual income provided that they hired at least 10 persons with disabilities at any job level. As though it were a trade-off, the 15% tax incentive was replaced with the special grant, a grant intended for persons with disabilities organized in small groups to generate income. The special grant started off as a pilot in 48 districts before it was rolled out nationally. Since 2019, the responsible ministry has been implementing two models of the special grant: the district special grant and the national special grant. This study focused on the district special grant, and primarily explored the experiences of persons with disabilities in accessing and utilizing the district special grant, and the difference the grant is making. The study adopted a qualitative research approach using interviews and focus group discussions to collect data from 10 beneficiary groups drawn from 6 districts. Focus group discussions were conducted with special grant beneficiary groups while district officials responsible for the special grant and disability union representatives were individually interviewed. Data were analyzed using template coding and thematic analysis. Study findings revealed limited access to the district grant, dismal grant amounts, significant deviations from implementation guidelines, operational dilemmas and overlooking disability related expenses like the costs for moving with a personal assistant. Nonetheless, participants commended the special grant for enabling them to build social networks, gain self-confidence and start small income generating activities. The small grant amount disbursed to big group size groups that lack business start-up skills did not support impactful business initiatives. The study revealed a strong evidence from individual grants as opposed to a group grants for starting income generating activities. The ministry of gender should consider remodeling the special grant into a social protection scheme that awards small grants to individual income generating activities.